2014
DOI: 10.1063/1.4862905
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the length dependence of molecular junction thermopower

Abstract: Thermopower of molecular junctions is sensitive to details in the junction and may increase, decrease, or saturate with increasing chain length, depending on the system. Using McConnell's theory for exponentially suppressed transport together with a simple and easily interpretable tight binding model, we show how these different behaviors depend on the molecular backbone and its binding to the contacts. We distinguish between resonances from binding groups or undercoordinated electrode atoms, and those from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
(76 reference statements)
2
22
0
Order By: Relevance
“…However, this lies within the predictions of the tunneling model as described in Ref. 26: β(E) exhibits a strong energy dependence and its derivative, β ′ (E), changes sign around the Fermi level. Since end groups can strongly influence the position of MO energies with respect to E F (alteration of the band lineup or level alignment) [45][46][47] they also effect β S = β ′ (E)| E=EF .…”
Section: B Length Dependencesupporting
confidence: 87%
See 1 more Smart Citation
“…However, this lies within the predictions of the tunneling model as described in Ref. 26: β(E) exhibits a strong energy dependence and its derivative, β ′ (E), changes sign around the Fermi level. Since end groups can strongly influence the position of MO energies with respect to E F (alteration of the band lineup or level alignment) [45][46][47] they also effect β S = β ′ (E)| E=EF .…”
Section: B Length Dependencesupporting
confidence: 87%
“…[20][21][22] Experimentally, it has been found that the thermopower increases linearly with the length of a molecular chain, N . 23,24 This is supported in theory for the off-resonant tunnelling regime, where the transmission is exponentially surpressed around the Fermi energy 25,26 τ…”
mentioning
confidence: 68%
“…The use of TB models to complement DFT calculations is rather common (see, e.g. [78][79][80][81]), and is useful for several reasons: (i) DFT calculations may become extremely computationally expensive and lengthy, (ii) the TB model allows for interpretation of the DFT calculation in terms of a simple physical picture, which is in many cases hard to build from the output of the DFT calculation (typically energies, orbitals and transmission), (iii) additional effects (such as dephasing, see below) cannot be introduced within the DFT calculation. The helicene molecule TB Hamiltonian is given by…”
Section: Results: Tuning Conductance and Thermopowermentioning
confidence: 99%
“…267 In addition, the effect of molecular length on ZT has been investigated, leading to the fundamental understanding of thermoelectric properties of single-molecule devices. [268][269][270][271][272][273][274][275][276] These studies indicate that an increase of molecular length results in an enhancement of the thermopower generation, but at the cost of a considerable decrease in electronic conductance. Therefore very long molecules may not be a good choice for the design of singlemolecule thermoelectric devices.…”
Section: Thermoelectric Power In Single-molecule Junctionsmentioning
confidence: 93%